Improved production of palitantin by design of experiments and semi-synthesis of palitantin derivatives for bioactivity assessment - Santucci, Pedro M.; de Oliveira, Caroline R.; Monteiro, Afif F.; Mendes, Giovana R.; de Amorim, Marcelo R.; Rosa, Gabriel H.S.; Sette, Lara D. [UNESP]; Marchi, Rafael C.; Deflon, Victor M.; dos Santos, Pedro H.T.; Carvalho, Gabriela G.; Brocchi, Marcelo; et al. (Elsevier, 2025)
A new method for the production and isolation of (+)-palitantin (1) is herein reported, from cultures of the fungal strain Penicillium sp. AMF1a. (+)-Palitantin was isolated in 160 mg/L yield, as an alternative procedure to obtain 1 at a larger scale. The complete spectroscopic characterization, including conformational analysis, is presented for (+)-palitantin (1) and for its derivatives 3-α-palitantol (2), 3-β-palitantol (3), (Z)-palinitrorin (4), (Z)-paliphenin (5), (Z)-palifluorin (6) and (E)-palifluorin (7). The absolute configuration of the palitantin portion was confirmed by X-ray analysis of compound 4. The (4-(trifluoromethyl)benzyl)-hydrazone derivatives (6 and 7) displayed moderate biological activities. (Z)-Palifluorin (6) exhibited moderate antiplasmodial activity, while (E)-palifluorin (7) displayed weak antibacterial activity against E. faecalis and S. aureus, while palitantin itself was inactive in the same bioassays, indicating that the semi-synthesis of nitrogenated derivatives of 1 may be of potential interest to generate bioactive palitantin derivatives.
Keywords: Antibacterial; Antiplasmodial; Derivatization; Fungal metabolites; Palitantin; Penicillium